Academic buildings as a substantial part of the teaching system. The case of the new building design at the School of Engineering, National University of Rosario, Argentina. Issue 3 (September 2019) - Piacentini, Ruben; Vega, Marcelo; Morabito, Julieta; Rene Estevez, Maria
Abstract: The population growth observed in the past decades demands that future buildings will have to include energy-efficiency measures as well as their own clean energy production plant, in order to be of very low or, if possible, positive net energy. This means that buildings will produce, on an annual basis, more energy than they will consume. The design of the new building for the School of Engineering, Faculty of Exact Sciences, Engineering and Surveying, National University of Rosario, Argentina, is given as an example of this kind of building. The building techniques applied in this design include: autoclaved aerated concrete in walls and insulation thermal roof panels, high energy and water consumption efficiency, photovoltaic power supply and sensors/dataloggers and actuators placed in the main equipment and sites. With these technological improvements, several analyses yielded reductions of 70%, in comparison with conventional buildings. Regarding the energy consumption of the facility, this is estimated at 29620 KWh/year, resulting in an energy intensity of about 25.7 KWh/(m 2 year). The energy annually produced by the PV plant (58491 KWh/year) exceeds what is required, which makes the facility a positive energy building in +49.4%, being this surplus exported to the National Electrical Interconnected System. The positive (clean) energy building implies that it avoids the emission to the atmosphere of a given quantity of greenhouse gases, in the present case 20647 TnCO2eq. In this way, through a comprehensive design of buildings, the construction sector can collaborate on the global contamination reduction and, consequently, global warming mitigation.